Altered gut microbiota and microbial biomarkers associated with chronic kidney disease - Hengzhong Lun; Weihua Yang; Shuping Zhao; Meijie Jiang; Mingjie Xu; Fenfen Liu; Yunshan Wang (MicrobiologyOpen, 2019)
Abstract The present study aimed to determine the differences in gut microbiota between patients with chronic kidney disease (CKD) and healthy controls (HC) and search for better microbial biomarkers associated with CKD. The 16S rRNA gene sequencing approach was used to investigate the differences in gut microbiota between the CKD and HC groups. The study found that 12 phylotypes were overrepresented in the CKD group and 19 in the HC group at the genus level. Furthermore, genera Lachnospira and Ruminococcus_gnavus performed the best in differentiating between HC and CKD populations. In addition, this novel study found that the genera Holdemanella, Megamonas, Prevotella 2, Dielma, and Scardovia were associated with the progression of CKD and hemodialysis. In conclusion, the composition of gut microbiota was different in CKD populations compared with healthy populations, and Lachnospira and R._gnavus were better microbial biomarkers. In addition, five phylotypes, including Holdemanella, Megamonas, Prevotella2, Dielma, and Scardovia, served as an indicator of the progression of CKD and hemodialysis. However, large‐scale prospective studies should be performed to identify the reliability of the set of these phylotypes as biomarkers.